Progress in wafer bonding technology towards MEMS, high-power electronics, optoelectronics, and optofluidics - Jikai Xu; Yu Du; Yanhong Tian; Chenxi Wang (International Journal of Optomechatronics, 2020)
Wafer bonding is an attractive technology that can join homo/heterogeneous materials into one composite. It has a wide range of applications in the micro-electro-mechanical system (MEMS), integrated circuit, consumer and power electronics, micro/nanofluidics, etc. Since all devices on the same wafer are sealed and tested at wafer size, it brings lots of benefits compared with the component-level packaging, such as substantial savings in time, materials, and labor. In this review, we firstly introduce the low- and room-temperature Si bonding and their applications in MEMS fabrication. Subsequently, we present applications of the third-generation semiconductor bonding towards optoelectronics. Due to the research in the electro-optical modulation of lithium niobate (LiNbO3) has made revolutionary progress in recent years, we also show the bonding method towards single-crystal LiNbO3 thin-film fabrication. Finally, we set our sights on the bonding of infrared materials, which might be the next research hotspot for the emerging ultrasensitive sensors.